New advances in clinical application of neostigmine: no longer focusing solely on increasing skeletal muscle strength - Si, Shangkun; Zhao, Xiaohu; Su, Fan; Lu, Hongxiu; Zhang, Dongbin; Sun, Li; Wang, Fulei; Xu, Li (Frontiers in Pharmacology, 2023)
Neostigmine is a clinical cholinesterase inhibitor that is commonly used to enhance the function of the cholinergic neuromuscular junction. Recent studies have shown that neostigmine regulates the immune-inflammatory response through the cholinergic anti-inflammatory pathway, affecting perioperative neurocognitive function. This article reviews the relevant research evidence over the past 20 years, intending to provide new perspectives and strategies for the clinical application of neostigmine.